2017
DOI: 10.14260/jemds/2017/1347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathological Profile of Patient With Solitary Thyroid Nodule in Tertiary Care Hospital in South India

Abstract: BACKGROUNDIncidence of malignancy in a solitary thyroid nodule is higher than in multinodular goitre. The prevalence of nodules in the general population is around 8% with greater predisposition in females. This study was undertaken to study the functional status of solitary nodules and to analyse the types of malignancy occurring in solitary nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…14 Present study gave us finding that 68% of population had benign lesions incidence with solitary thyroid nodule.One study showed that Solitary Nodule of Thyroid was more common in female participants with incidence of Malignancy of 8%. 15 In our present study findings we discovered 100% of the population having swelling in neck as a clinical feature presented with solitary thyroid nodule while palpitation and dyspnoea were least observed. Our findings matched the conclusion given by a case study of solitary thyroid nodule.…”
Section: Discussionsupporting
confidence: 52%
“…14 Present study gave us finding that 68% of population had benign lesions incidence with solitary thyroid nodule.One study showed that Solitary Nodule of Thyroid was more common in female participants with incidence of Malignancy of 8%. 15 In our present study findings we discovered 100% of the population having swelling in neck as a clinical feature presented with solitary thyroid nodule while palpitation and dyspnoea were least observed. Our findings matched the conclusion given by a case study of solitary thyroid nodule.…”
Section: Discussionsupporting
confidence: 52%
“…Incidence rate The present study 18% Fenn et al [13] 12% Bhansali SK et al [14] 09% Rehman AU et al [15] 11% Naz Akhtar et al [16] 15.3% Historically, surgeons would perform routine surgical removal for every solitary thyroid nodule, but such a radical approach led to a tricky conundrum wherein many patients underwent unnecessary surgery for a STN that later turned out to be a benign lesion on histopathological examination.…”
Section: Studiesmentioning
confidence: 76%
“…Table 3 shows the comparison of incidence of Malignancy in solitary thyroid nodule with other studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation